(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe work motivation and analyze some factors related to work motivation groups of medical staff at Vietnam - Russia International Eye Hospital in 2025. Method: A cross-sectional descriptive study on 350 medical staff of 3 facilities of Vietnam - Russia International Eye Hospital. Using a set of questions, anonymous interviews via Google Form. Results: Among the 5 groups of work motivation, the motivation to work on achievement accounted for the highest rate of 65.3%; the motivation to work on responsibility accounted for the second highest rate 62.5% and the lowest was the motivation due to recognition of achievement (41.8%). Some factors related to work motivation: income level is the strongest factor related to work motivation, especially the motivation group of work responsibility (adjOR = 1.72, p < 0.05); men tend to have lower motivation to work than women, especially motivation for promotion opportunities (adjOR = 0.45, p < 0.05); the group under 40 years old is no less motivated to work than the group aged 40 and over; highly educated groups tend to be more motivated, especially motivated to be responsible for their work. Motivating factors, favorable at work, and rational management have a strong impact on motivation for achievement and development opportunities (adjOR from 1.4 to 1.79), but not for other motivation groups. Conclusion: The motivation of medical staff is quite good. The factor that has the strongest impact on work motivation is income level.